ANALISIS YURIDIS TENTANG RANCANGAN UNDANG-UNDANG HALUAN PANCASILA - Muhammad Rizqi Fadhlillah; Yusmedi Yusuf (SUPREMASI HUKUM, 2021)
Pancasila, which has become an ideology of the state, is currently facing a polemic with the Draft of the Pancasila Ideology (RUU HIP) proposed by members of the DPR. This polemic arose because the absence of TAP MPRS NUMBER 25 / MPRS / 1966 of 1966 concerning the Disbanding of the Indonesian Communist Party, Statement as a Prohibited Organization in the Entire Territory of the Republic of Indonesia and the Prohibition of Every Activity to Spread Or Develop Communist / Marxist-Leninism and Pancasila Doctrine has been conceived to be squeezed into Trisila and Ekasila. The research method used in this study is normative research. The existence of the Draft Bill of Ideology is considered to change the basis of the state and change the state and national life order of the Indonesian people, therefore the Draft of the Pancasila Ideology Bow course must be rejected. Keywords : Draft Law; Pancasila; Ideology.